Faktor-faktor Yang Mempengaruhi Pengekalan Pekerja di Sarawak Electricity Supply Coperation (SESCO) - Saharun, Yusop (Universiti Malaysia Sarawak, (UNIMAS), 2005)
The purpose of this research is reviewing factors that influencing retention of workers in an organization. This research take place at Sarawak Electricity Supply Corporation (SESCO) and 43 respondents were involved in the research. Random sampling technique was used to select the respondents. The methodology used in this research was questionnaires. About 43 forms of questionnaire have been distributed and the data were analyzed. Three testing method were used like One-Way ANOVA, T-test and Pearson Correlation. The findings showed that there is no significant differences between age and retention of workers). This research also showed that there were no significant difference in retention of workers between gender, married status and monthly salary. There was significant relationships between communication and retention of workers, supervision and retention of workers and work environment and retention of workers. Relation among factors communication and supervision towards retention of workers is moderate. Relation among factor of work environment towards retention of workers is weak. Therefore, the organization should be more concern of all the factors that can influence the retention of workers. Otherwise, if these factors are not stated in the strategy and organization planning, it will cause problems in retaining workers in the organization